Underestimation of clinical importance of non-steroidal anti-inflammatory drug induced enteropathy and its exacerbation by proton pump inhibitors - Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2012)
DOI: http://dx.doi.org/10.3126/jaim.v1i2.6502 Journal of Advances in Internal Medicine 2012;01(02):50-2